LncRNA HOXA11-AS promotes proliferation and invasion by targeting miR-124 in human non–small cell lung cancer cells - Wanjun Yu; Weidong Peng; Hao Jiang; Hanyun Sha; Jipeng Li (Tumor Biology)
Long non-coding RNAs have been implicated in human cancer but their mechanisms of action are mainly undocumented. In this study, we found that HOXA11-AS expression was upregulated in non–small cell lung cancer tissues and cell lines. High levels of HOXA11-AS expression were correlated with larger tumor size and lymph node metastasis. Functional analysis revealed that HOXA11-AS promotes non–small cell lung cancer cell proliferation and invasion. In particular, HOXA11-AS functions as a competing endogenous RNA to regulate transcriptional factor Sp1 expression via sponging miR-124. Collectively, our findings reveal an oncogenic role for HOXA11-AS in non–small cell lung cancer tumorigenesis.